Geomorpho-pedological context of the landscape units with open-air archaeological sites in the Currais de Pedra region, Northern Minas Gerais - Alves Pereira, Carla Cristina; de Oliveira, Fabio Soares; Rodet, Maria Jacqueline; Alkimin de Sá, Lorena (Revista Brasileira de Geomorfologia, 2025)
The Karst Region of Currais de Pedra, located in northern Minas Gerais, Brazil, holds a significant archaeological and speleological heritage, with sites containing rock art, ceramic fragments, and lithic remains. Despite its recognized importance, the region remains little known, being gradually revealed through geomorphological and geoarchaeological studies. This study focuses on the landscape units known as Limestone Massifs and Intermassif Slopes, which are conducive to past human occupation and host the open-air archaeological sites of Ressurgência and Conceição Caetano. We aimed to detail the physical-environmental framework of these units, emphasizing the organization of landforms at the fourth taxonomic level and characterizing the main soils that constitute the surficial deposits of the sites. Field and laboratory procedures were employed, including aerophotogrammetric surveys, landform mapping, and soil sampling and analysis. The results indicate that human groups appropriated the landscape by favoring geomorphological features such as intermediate plateaus and limestone slabs within the massifs, as well as colmated valleys. These areas were identified as the most favorable for the formation of open-air archaeological sites. Soil analyses revealed anomalies of phosphorus enrichment with distinct origins. At sites like Conceição Caetano, these anomalies are associated with more permanent or long-term human occupations. In contrast, at areas such as Ressurgência, the enrichment is linked to more sporadic occupations and the activity of local fauna, attracted by fertile soils and the presence of forest patches.